IS THERE A SEX-RELATED DIFFERENCE IN ENDOTHELIUM-DEPENDENT MICROVASCULAR RESPONSE TO ACUTE SALT LOADING IN YOUNG HEALTHY INDIVIDUALS?. (June 2018) - Stupin, M.; Stupin, A.; Rasic, L.; Matic, A.; Kolar, L.; Mihaljevic, Z.; Drenjancevic, I.
Abstract : Objective: We have earlier reported that acute salt loading affects acetylcholine (ACh) induced vasodilation (endothelium-dependent) in forearm skin microcirculation in young healthy women independently of blood pressure (BP) changes. The aim of the present study was to test is there a sex-related difference in endothelium-dependent forearm skin microvascular response to acute salt loading in young healthy individuals. Design and method: 16 young healthy men participated in this study (age range 19–24). All subjects took 7-days low-salt (LS) diet – washout period (<3.2 g salt/day) followed by 7-days HS diet (∼14 g salt/day). Skin microvascular blood flow measurement was done using Laser Doppler Flowmetry in response to iontophoresis of acetylcholine (ACh) before and after diet protocols. BP and heart rate (HR) were measured at the beginning of each visit (mean of three repeated measurements). 24h-urine sodium, potassium, urea and creatinine levels were measured before and after diet protocols. Salt intake was estimated based on calculation of 24-hour urinary sodium excretion. Results: Changes in 24 h urinary sodium excretion and calculated salt intake confirmed that subjects conformed to the diet protocols. There was no significant difference in BMI and WHR before and after HS diet. There was no change in BP and HR before and after HS diet. In accordance with our earlier results obtained in young healthy women (flow change compared to basic flow: before HS diet 1797 ± 523 vs. after HS diet 1309 ± 751, P = 0.024; Physiology 2016), ACh induced dilation was significantly impaired after HS diet protocol in young healthy men as well (flow change compared to basic flow: before HS diet 2157 ± 1048 vs. after HS diet 1592 ± 586, P = 0.014). Conclusions: The results of the present study demonstrated that 7-days HS diet impairs forearm skin microvascular ACh-induced dilation independently of BP changes in young healthy men, just as we earlier reported in women. Eventhough there are many known sex-related differences in various cardiovascular responses even in healthy individuals, the results of this study suggesst that one week HS loading affects endothelium-dependent vasodilation in peripheral microcirculation correspondingly in young healthy men and women.